2020
DOI: 10.1002/cam4.2868
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 inhibitors for non‐small cell lung cancer patients with special issues: Real‐world evidence

Abstract: Background Immune checkpoint inhibitors (ICIs) have provided new therapeutic options for non‐small cell lung cancer(NSCLC) patients. However, due to concerning increases in immune‐related adverse events, clinical trials usually exclude patients with special issues such as viral hepatitis, tuberculosis (Tbc), interstitial lung disease (ILD) and autoimmune disease. Methods We retrospectively reviewed the medical records of NSCLC patients who received ICIs, and analyzed the clinical outcomes of patients with spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 36 publications
2
47
0
Order By: Relevance
“…These results are shown in Table 3 and Figure 1. (14)(15)(16)(17)(18)(19)(20). Most of the relevant studies have enrolled a limited number of patients, impeding in-depth characterization of the safety and efficacy of immunotherapy.…”
Section: Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…These results are shown in Table 3 and Figure 1. (14)(15)(16)(17)(18)(19)(20). Most of the relevant studies have enrolled a limited number of patients, impeding in-depth characterization of the safety and efficacy of immunotherapy.…”
Section: Efficacymentioning
confidence: 99%
“…Recently, some retrospective studies or prostective clinical trials have demonstrated that the efficacy and limited toxicity of PD-(L)1 inhibitors in patients with HIV infection and advanced NSCLC is similar to non-infected patients (9)(10)(11)(12)(13). However, data from the literature have been limited to case reports or small case series that have described the utilization of PD-1 pathway inhibitor (alone or in combination with ipilimumab or chemotherapy) for advanced NSCLC patients with chronic or previous HBV infection (14)(15)(16)(17)(18)(19)(20). Therefore, there is a paucity of information on the safety and efficacy of anti-PD-(L)1 monotherapy in this population.…”
Section: Introductionmentioning
confidence: 99%
“…None of the patients had HCV reactivation or HCV-associated hepatitis. 225 In a study by Byeon et al 225 it was found that among 237 patients with NSCLC treated with anti-PD-1, 14% had HBV infection. The ORR was 23.1%.…”
Section: Patients With Viral Infections Such As Hepatitis B and C And Hivmentioning
confidence: 99%
“…Furthermore, the PD-1/PD-L1 pathway suppresses the accumulation of CD4 + T-cells and IFN-γ production, which is an essential part of the immune response to TB. However, treatment that targets PD-1/PD-L1 may cause CD4 + T-cells to overproduce IFN-γ, which can aggravate TB or cause TB recurrence (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Another study has indicated that a TB antigen can inhibit the Th1 immune response and promote LC metastasis via the PD-1/PD-L1 signalling pathway (36).…”
Section: Discussionmentioning
confidence: 99%